Warm, but not hypoxic acclimation, prolongs ventricular diastole and decreases the protein level of Na+/Ca2+exchanger to enhance cardiac thermal tolerance in European sea bass - Pettinau Luca; Lancien Frédéric; Zhang Yangfan; Mauduit Florian; Ollivier Hélène; Farrell Anthony P; Claireaux Guy; Anttila Katja (ELSEVIER SCIENCE INC, 2022)
One of the physiological mechanisms that can limit the fish's ability to face hypoxia or elevated temperature, is maximal cardiac performance. Yet, few studies have measured how cardiac electrical activity and associated calcium cycling proteins change with acclimation to those environmental stressors. To examine this, we acclimated European sea bass for 6 weeks to three experimental conditions: a seasonal average temperature in normoxia (16 °C; 100% air sat.), an elevated temperature in normoxia (25 °C; 100% air sat.) and a seasonal average temperature in hypoxia (16 °C; 50% air sat.). Following each acclimation, the electrocardiogram was measured to assess how acclimation affected the different phases of cardiac cycle, the maximal heart rate (fHmax) and cardiac thermal performance during an acute increase of temperature. Whereas warm acclimation prolonged especially the diastolic phase of the ventricular contraction, reduced the fHmax and increased the cardiac arrhythmia temperature (TARR), hypoxic acclimation was without effect on these functional indices. We measured the level of two key proteins involved with cellular relaxation of cardiomyocytes, i.e. sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA) and Na+/Ca2+ exchanger (NCX). Warm acclimation reduced protein level of both NCX and SERCA and hypoxic acclimation reduced SERCA protein levels without affecting NCX. The changes in ventricular NCX level correlated with the observed changes in diastole duration and fHmax as well as TARR. Our results shed new light on mechanisms of cardiac plasticity to environmental stressors and suggest that NCX might be involved with the observed functional changes, yet future studies should also measure its electrophysiological activity.